Immune checkpoint inhibitor-induced diabetes mellitus: clinical characteristics and risk factors - Zhan, Mei; Long, Qinran; He, Jinhan; Huang, Litao; Wu, Bin; Xu, Haixia; Mo, Li; Xu, Ting (Frontiers in Immunology, 2025)
BackgroundEmerging evidence indicates that immune checkpoint inhibitor-induced diabetes mellitus (ICI-DM) might be more common than initially reported, and more different clinical pictures associated with ICI-DM were described.ObjectiveThe aim of our study was to identify the clinical characteristics and possible predictive factors of ICI-DM.MethodsWe conducted a retrospective review of patients who received immune checkpoint inhibitors (ICI) at West China Hospital, Sichuan University until June 2023. Patients were reviewed at death or on 7 May 2024. We applied logistic regression to study the associations between clinical characteristics and ICI-DM.ResultsOur study included 8,199 participants who received ICI between October 2014 and June 2023. Among them, 1,077 patients (13.14%) developed ICI-DM according to diagnostic criteria based on guidelines. By excluding patients influenced by glucocorticoids or immunosuppressants, ICI-DM was observed in 713 of 8,199 (8.70%) patients. In all patients, hypertension, hyperlipidemia, using glucocorticoids or immunosuppressants, lung cancer, and using more than one pathway of ICI were associated with a higher risk of ICI-DM. However, the risk factors for ICI-DM in patients without the influence of glucocorticoids or immunosuppressants were only hypertension, hyperlipidemia, and pancreatic lesions. In all patients and those patients without the influence of glucocorticoids and immunosuppressants, hypertension and hyperlipidemia may increase the risk for ICI-DM.ConclusionsThis large, real-world cohort demonstrates that the incidence of ICI-DM may be underestimated in previous literature. Blood glucose monitoring is needed in patients receiving ICI therapy.Clinical trial registrationhttps://www.chictr.org.cn, identifier ChiCTR2300075974.